OP0028 The Disease Modifying Effect of Strontium Ranelate in a Phase III Knee Osteoarthritis Study (SEKOIA) Using Quantitative Magnetic Resonance Imaging: Reduction in Bone Marrow Lesion Size Associated with Cartilage Protective Effect. (23rd January 2014) - Martel-Pelletier, J.; Roubille, C.; Raynauld, J.-P.; Abram, F.; Dorais, M.; Delorme, P.; Pelletier, J.-P.
Abstract : Objectives: To explore using quantitative magnetic resonance imaging (qMRI) the disease modifying effect of strontium ranelate (SrRan) treatment on the cartilage volume loss and bone marrow lesions (BMLs) in a subgroup of patients from a Phase III clinical trial on human knee osteoarthritis (OA) (SEKOIA). Methods: Patients with primary symptomatic knee OA were randomized to receive either SrRan 1 g or 2 g/day or placebo. MRI was performed at baseline, 12, 24, and 36 months. The changes in knee cartilage volume loss and BMLs were assessed in the global joint and subregions. Missing values were imputed and the analyses were adjusted according to Bonferroni. Results: In the subgroup of patients with MRI, the distribution of patients (n=330) was 113, 105, and 112 for SrRan 1 g/day, 2 g/day, and placebo, respectively. There were no between-group differences at baseline with regard to demographics, clinical symptoms, or imaging characteristics. Treatment with SrRan at 2 g/day significantly decreased the loss of cartilage volume on the tibial plateau at 12 (p=0.002) and 36 months (M36) (p=0.003). At M36, in patients with BML at baseline, the BML score decreased in the two treatment groups compared to an increase in the placebo group in the medial compartment (p=0.002 and p=0.001 in the SrRan 1 g/day and 2 g/day groups, respectively). In those patients, SrRan 2 g/day significantly (p=0.023) decreased the cartilage loss at M36 in the medial tibial plateau compared to placebo, whereas SrRan 1 g/day did not (p=0.763). Conclusions: In knee OA patients, treatment with SrRan 2 g/day was found to have a beneficial effect both on cartilage and subchondral bone by significantly reducing the cartilage volume loss in the tibial plateau and the progression of BML in the medial compartment. Disclosure of Interest: J. Martel-Pelletier Shareholder of: ArthroLab Inc, Grant/research support from: Servier, Consultant for: Servier, ArthroLab Inc, C. Roubille: None Declared, J.-P. Raynauld Consultant for: ArthroLab Inc, F. Abram Employee of: ArthroLab Inc., M. Dorais: None Declared, P. Delorme: None Declared, J.-P. Pelletier Shareholder of: ArthroLab Inc, Grant/research support from: Servier, Consultant for: Servier, ArthroLab Inc